Rewrite the function in standard form.

y=(x+4)(x+3)

2 answers

y=x^2 +7x+12;; f (x) = a(x - h)2 + k, where (h, k) is the vertex of the parabola. FYI: Different textbooks have different interpretations of the reference "standard form" of a quadratic function. Some say f (x) = ax2 + bx + c is "standard form", while others say that f (x) = a(x - h)2 + k is "standard form".
the other is
(x+7/2)^2 -.5=0
I don't understand the answer. Could you explain it a bit more. Just trying to understand a little better.